Homosexual and Heterosexual University Students’ Attitudes Toward Prostitutes and Prostitution in Bogotá - Moreno, Paula Andrea; Girón, Ximena; Lugo, Alejandra; Forero, Daniel; Riveros Múnevar, Fernando; Vera Maldonado, Luis Anderssen; Vargas Rubio, Claudia Victoria; Forero Aponte, Carlos; Duque, Luis Carlos (Pensando Psicología, 2018)
This is a descriptive study whose group comparison analysis method aimed to identify differences in attitudes toward prostitutes and prostitution on the part of homosexual and heterosexual university students in Bogotá. To this end, the Attitudes Toward Prostitutes and Prostitution Scale was administered to 162 university students from Bogotá between 18 and 27 years old. Results show that there are no differences in attitudes toward prostitutes by groups, but there are differences in attitudes towards prostitution because heterosexual university students had a more negative attitude towards it than homosexual university students.